TRENDS IN THE DEVELOPMENT OF VIRTUAL REALITY TOOLS IN THE GLOBAL DESIGN PRACTICE - Shataliuk, Yu.; Shataliuk, D. (Municipal economy of cities. Series: «Economy science», 2023)
The article is devoted to consideration of general trends in the development of virtual reality in architecture. It has been determined that the conditions for the usage of VR in architecture are becoming more and more favourable as each year these technologies are improved and their availability increases. As a result of the increasingly widespread use of smartphones, virtual reality applications have appeared that can be easily downloaded and installed on a phone. From the variety of tools for working with virtual reality, those that can be useful for applicability in architecture were selected. The chosen relevant tools were systematised into two categories: hardware and software. Recommendations for their application, depending on the request or stage of the project, are presented. It has been determined which form of virtual reality, devices, and software are the most suitable for the analysis, simulation, and design of the architectural environment. Special attention in the research is paid to artificial intelligence and the analysis of its influence on VR in architecture. The speed of development, compared to the traditional methods, economic expediency, and enhanced realism are singled out among the advantages of artificial intelligence. The prospects for VR development in architecture and its impact on the profession are examined. VR can also be used to create innovative new designs for buildings, allowing architects to explore the potential of materials, textures, and shapes in a way that was not possible before. Architects and designers can use VR to create, experimentalise, and refine design solutions virtually before starting construction. In the future, VR will become an integral part not only of the design process but also of presentation and approval. It is a powerful tool that helps establish communication between all the process participants. VR in architecture has enormous potential, the implementation of which will provide high social and economic results.